POLAR STAR Roadmap: Showing the way to innovative learning - (:unkn) unknown (fi=Turun yliopisto|en=University of Turku|, 2023)
We couldn’t be happier to present to you our POLAR STAR roadmap! This book encompasses all the work we have done during the past three years, in an effort to continue offering teachers solutions that will help them bring innovation and state-of-the-art practices to their school class. To us, teachers are the silent heroes that have the privilege and responsibility to shape students’ minds and help them grow into individuals fully equipped to find their own way into an increasingly volatile and rapidly changing world. As you are our heroes, we wanted to make sure that the work we did in POLAR STAR is meaningful and helpful to you. To that end, during our three-year journey we worked with as many of you as possible and we were happy to involve teachers in every aspect of the project. What you will read in this book has been co-designed with advisor teachers and pilot tested in schools across Europe. Browsing through this book, you will learn about our methodology which we originally started designing during the PLATON project and we have completed in POLAR STAR. Using this methodology, you will be able to teach the required content while developing students’ key competences through means that are closely related to students’ everyday life and contemporary societies. Strong emphasis is also given on personalizing the learning process, formative feedback and the promotion of horizontal connectedness across learning disciplines through interdisciplinary episodes of learning. In this book you will also find a set of activities on Arctic research and Space exploration. Students often believe contemporary science to be completely disconnected to their needs and the world. Also, they are often found to believe that they are not fit to following scientific careers and they dismiss them for being too difficult, complicated, or impossible to pursue. Our activities will help your students obtain a clear understanding of the strong bond between science, technology and society, develop an appreciation of what science and technology offers to the world and most importantly cultivate the idea that scientific careers can be exciting, rewarding and that they are ‘there for the taking’ by boys and girls alike. We hope you enjoy reading our roadmap and that it will inspire you to use POLAR STAR with your students!